Baptism in the New Testament - Beasley-Murray, George Raymond, 1916-2000 (Exeter, UK Paternoster, 1972)
Includes bibiographical references and indexes.
Keywords: Baptism -- Biblical teaching; Bible. N.T. -- criticism, interpretation, etc